2021
DOI: 10.3389/fmicb.2021.762689
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Phaffia rhodozyma Astaxanthin on Growth Performance, Carotenoid Analysis, Biochemical and Immune-Physiological Parameters, Intestinal Microbiota, and Disease Resistance in Penaeus monodon

Abstract: The present study aimed to investigate the effect of dietary astaxanthin (Ast) from Phaffia rhodozyma on growth performance, survival, carotenoid content, the activity of antioxidant and immune-related enzymes, intestinal microbiota comparison, and disease resistance against Vibrio parahaemolyticus in Penaeus monodon. Juveniles (average weight 3.15 ± 0.12 g) were fed with six experimental diets supplemented with 0 (Control), 20.5, 41, 61.5, 82, and 102.5 mg/kg of Ast (defined as diet A–D) in triplicate for 56 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…This phenomenon was supported by our study whereby higher dietary protein dramatically improved growth performance compared with the lower protein level in the diet; however, optimum PER was observed at a middle protein level. At present, many studies have provided evidence whereby appropriate supplementation of astaxanthin in diet could improve growth performance in Litopenaeus vannamei and Penaeus monodon (Liu et al, 2022; Wang et al, 2021; Zhao et al, 2022). However, this does not correspond with other studies whereby growth performance was not affected by astaxanthin in crustaceans (Han et al, 2018; Jiang et al, 2020; Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was supported by our study whereby higher dietary protein dramatically improved growth performance compared with the lower protein level in the diet; however, optimum PER was observed at a middle protein level. At present, many studies have provided evidence whereby appropriate supplementation of astaxanthin in diet could improve growth performance in Litopenaeus vannamei and Penaeus monodon (Liu et al, 2022; Wang et al, 2021; Zhao et al, 2022). However, this does not correspond with other studies whereby growth performance was not affected by astaxanthin in crustaceans (Han et al, 2018; Jiang et al, 2020; Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Sanderson and Jolly 111 claimed P. rhodozyma to affect the characteristics of salmonids products by colouring them. In a recent study, Wang et al 112 reported dietary P. rhodozyma played a major role in improving growth, health performance, and achieving desired coloration as an alternative to synthetic astaxanthin in HAPP‐based diet of Penaeus monodon . Consequently, developing novel natural sources of carotenoids and improving processing technologies to produce them from natural sources must be prioritized in research for future uses of carotenoids in aquafeeds in order to meet customer demand for natural colouring pigments.…”
Section: General Classification Of Fufa Used In Aquafeeds: An Overvie...mentioning
confidence: 99%
“…Information about the effect of Ax on gut microbiota in food animals is scarce. Only Wang et al. (2021b) argued that intestinal microbiota biodiversity and richness were unaffected by dietary Ax from P. rhodozyma in shrimp.…”
Section: Application Of Astaxanthin In Laying Hensmentioning
confidence: 99%